Measles vaccination of children born to HIV-infected mothers (clinical and immunological aspects) - N. F. Snegova (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Vaccination of children born to HIV-infected mothers in accordance with the national Calendar of preventive vaccinations represents an important issue. Upon that, measles incidence rate especially among unvaccinated children has been substantially elevated. Use of live measles vaccine in both HIV-infected children and mothers has some features primarily due to HIV-associated immunocompromised state that was poorly investigated. Here we monitored 212 children aged 12–36 months born to HIV-infected women, 184 HIV-negative children born to HIVinfected women who were included into the group with the diagnosis “Perinatal HIV contact” (R75) after verification. In addition, 28 children were included into the group” HIV infection “(B23), whereas 42 children — into the control group. Live measles vaccine was administered subcutaneously at a dose of 0.5 ml. All children were followed up for 36 weeks. HIV status, measles antibodies level by measured by ELISA and RPG methods, as well as total immunoglobulin A, M, G classes and CD3+, CD4+, CD8+, CD19+ lymphocyte counts were examined. No post-vaccination complications or severe vaccine-induced reactions were reported in HIV-infected patients group. A satisfactory course of the vaccine process in all children born to HIV-infected mothers was observed that did not significantly differ from that one in control group. Children with perinatal HIV contact are able to respond adequately to vaccination with live measles vaccine. The number of children with conditionally protective antibody levels, still remaining seronegative among children with perinatal HIV contact (R75) was comparable to that one in healthy control group. At the same time, children with perinatal HIV contact were shown to display protective antibody level after administering live measles vaccine only in 36.4% of cases, whereas the remainder (63.6%) demonstrated a conditionally protective antibody level or lack it (compared to 76% of children with perinatal HIV contact). Children with perinatal HIV infection who did not respond to the first administered live measles vaccine produced low amount of antibodies after re-vaccination. Seroconversion was observed in up to 68% of cases, whereas protective antibody level was found in up to 33.6% of child ren. On the contrary, children from the perinatal HIV contact group were shown to have protective antibody level in 69.6% of cases upon seroconversion rate reaching 91.3% that did not differ them from those in control group. In the post-vaccination period, suppressive modality of immune reaction tended to increase indirectly evidenced by increased percentage of CD8+ T cell subset.